AVALIAÇÃO COPROPARASITOLÓGICA EM CRIAÇÃO DE SUÍNOS NO MUNICÍPIO DE PARAIPABA, CEARÁ - Rocha, Mylano Viana da; Leite, Nayara Martins; Bezerra, Narjara Nadja; Silva, Michelle Costa e (Ciência Animal, 2021)
Parasitic diseases occupy a prominent place among swine pathologies. The losses go from mortality to morbidity. The degree of contamination depends on the production system used, the way of handling and the hygiene conditions. In the municipality of Paraipaba in the state of Ceará, the prevalence of gastrointestinal parasites in pig farms is unknown. Thus, this study aimed to analyze through coproparasitological exams the presence of gastrointestinal parasites in swine from a farm in the municipality of Paraipaba, in the state of Ceará. The pig farm, which keeps a total of 100 animals among breeders, breeders and piglets in the nursing, growth and finishing phases were collected directly from the rectal ampoule, made from the feces of 50 pigs of different ages, chosen randomly, to conduct research on protozoa and helminths through direct examination techniques, Willis technique, sedimentation and zinc flotation. In optical microscopy it was observed that of the 50 animals collected, 20% had oocysts of Cystoisospora sp. and 28% had Strongyloides sp. The high percentage of gastrointestinal parasites in swine raised in the municipality of Paraipaba warns of inadequate handling and hygiene conditions as these animals are reared, predisposing to infestation of gastrointestinal parasites in animals that cause damage to their health, as well as production and losses due to increase in the number of deaths.